Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5944/reop.vol.22.num.1.2011.78
|View full text |Cite
|
Sign up to set email alerts
|

El papel de la Inteligencia Emocional en la resolución de problemas sociales en estudiantes adolescentes / The role of Emotional Intelligence in solving social problems in a sample of adolescent’s students

Abstract: RESUMENLa presente investigación, con una muestra de 217 adolescentes, se centra en el análisis de la relación entre la inteligencia emocional percibida (IEP) y el grado en que el estudiante afronta y soluciona problemas sociales. Los resultados evidenciaron el valor predictivo e incremental de la IEP en relación a la resolución de problemas sociales controlando las variables demográficas (sexo y edad). Los análisis de regresión jerárquica por pasos muestran que la dimensión de Claridad emocional predice parte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Emotional intelligence (EI) is a construct that refers to the processes of recognition, understanding and regulation of our emotional states and of others, as well as their implementation to solve problems and regulate behaviour [1]. It has aroused great interest among researchers, being widely studied in different areas such as physical and mental health [2][3][4][5][6], education [7], sports, work, and organisations [8][9][10][11][12], among others, proving its importance and impact in all them [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional intelligence (EI) is a construct that refers to the processes of recognition, understanding and regulation of our emotional states and of others, as well as their implementation to solve problems and regulate behaviour [1]. It has aroused great interest among researchers, being widely studied in different areas such as physical and mental health [2][3][4][5][6], education [7], sports, work, and organisations [8][9][10][11][12], among others, proving its importance and impact in all them [13].…”
Section: Introductionmentioning
confidence: 99%
“…Higher EI is associated with a healthier emotional and physiological response and less use of avoidance, ignoring, or distraction strategies to cope with stressful situations [26]. Likewise, it has been related to adequate coping with stressful situations [27][28][29], motivation [30,31], problem-solving [7], self-esteem [32], adaptive use of emotions [3], and less disruptive behaviour [16,33]. These aspects are fundamental because the fulfilment of responsibilities is one of the most important factors for individuals to achieve success [34].…”
Section: Introductionmentioning
confidence: 99%
“…Esto quiere decir que la percepción de las mujeres sobre los afectos positivos en su vida está determinada por el optimismo, es decir, las mujeres que suelen tener expectativas positivas generalizadas acerca de las probabilidades de ocurrencias positivas en el futuro tendrán mayores afectos positivos. De la misma forma, se advierte que la reparación y claridad emocional influye directamente en la AP, o sea que cuando utilizan diferentes estrategias de afrontamiento adaptativas para resolver un problema, por lo general, no evitan las dificultades, sino que existe una mayor tendencia a resolver los problemas racionalmente (Pena et al, 2011). Al revisar el modelo predictivo de las mujeres para los AN, se evidencia que el modelo está determinado por seis variables que explicarían el 35,3 % de la varianza.…”
Section: Discusión Y Conclusionesunclassified
“…Personal development acquires importance as a formula to develop emotional aspects in the educational field, since, as Fernández-Berrocal [3] explains, reality has changed, and it no longer has as a priority to develop intellectual and academic aspects, but rather, it is necessary to face emotional and social aspects at the educational level. Here, various investigations have shown that students lack the psychological resources that allow them to successfully cope with problems associated with negative behavior and emotional difficulties at school [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%